Cuidados de higiene e de saúde de uma comunidade monástica do séculoXVII : o caso do Mosteiro de Santa Clara-a-Velha de Coimbra - Leal, Catarina Cunha; Ferreira, Manuela Almeida (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The studies in daily life’s material cultural should not forget the body care, as well in health as in illness. This article deals with archaeological finds excavated in the Monastery of Santa Clara-a-Velha in Coimbra (Portugal). The nuns of this community, a branch of the Franciscan Order, left us buried artefacts that tell us about daily worries concerning hygiene and recovering from diseases determined by the scientific study on skeletons buried indoors. Written sources are concealed to explain the use of certain herbs, the composition of apothecaries and the contexts of use of several vases and tools. We precede the approach of the finds by an overview about the main means of diagnostic and therapeutics in the 16th and 17th centuries.